Dewan Komisaris Independen, Komite Audit, Firm Growth, Leverage dan Manajemen Laba - Dwija Putri, I Gusti Ayu Made Asri; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi; Vol 33 No 12 (2023), 2023)
Profit information is of particular concern to investors and potential investors in assessing management performance. The company's demand to achieve predetermined profit targets motivates management to carry out profit management practices so that the resulting financial reports look good to investors. The aim of this research is to obtain empirical evidence of the influence of the independent board of commissioners, audit committee, firm growth and leverage on earnings management. This research was conducted on health sector companies listed on the Indonesia Stock Exchange for the 2016-2020 period. Determining the number of samples used a purposive sampling technique and a sample of 50 observations was obtained. The data analysis technique is multiple linear regression analysis. The results of this research show that the Independent Board of Commissioners has no effect on earnings management, the audit committee has no effect on earnings management, firm growth has a negative effect on earnings management, and leverage has a positive effect on earnings management. Keywords: Profit management; Board of Commissioners; Audit Committee; Firm Growth; Leverage